Implementation Of Hidden Curriculum in Shaping Professionalism and Islamic Professional Behavior: A Correlation Study in Nursing Students - Candra Dewi Rahayu; Ika Purnamasari; Sri Mulyani; Fifi Alviana; Nazila Nugraheni; Tantut Susanto (PT.Mantaya Idea Batara, 2025)
Introduction:Both professionalism and professional behavior (PB) are important in nursing education. An explicit and/or implicit curriculum, determined by higher education, is required to achieve this. The Hidden Curriculum (HC) foundation is described as the result of education outside the formal and informal curricula, as a complement and support of the curriculum, to create a stable, strong, and professional nursing education. Purpose: This study aims to explore the relationship between the Hidden Curriculum and professionalism and Islamic professional behavior in nursing students. Methods: The study used a cross-sectional design and included 181 students and 82 clinical supervisors. Data were collected using the Hidden Curriculum in Nursing Education Scale (HCES-N) questionnaire, as well as professionalism and professional behavior (PB) questionnaires developed based on the Indonesian Nursing Competency Standards.Results: The results indicate that the hidden curriculum significantly influences the academic atmosphere and professional knowledge. However, it does not affect educational facilities, student–lecturer interaction, or professional attitude. Overall, the hidden curriculum contributes to the development of professionalism and Islamic professional behavior. Conclusion and suggestion: Nursing higher education institutions should apply the hidden curriculum to cultivate a generation of nurses who are professional and possess Islamic character.